Studying Knowledge Distribution in Highly Dynamic and Poorly Known Situations - Hill, Martin (Cranfield University, 2018)
3MT presented at the 2017 Defence and Security Doctoral Symposium.This presentation outlines some of the problems, solutions and mitigations to studying knowledge distribution for the battlefield. It covers identifying, measuring and controlling variables to support experiments and case studies, and the use of ‘experimental method’ to identify ‘sweet spots’ in response surfaces to changing variables. It also offers a software implementation of a distribution simulation.
Keywords: 'Knowledge Distribution'; 'Uncertain Knowledge'; 'Intelligence Analysis'; 'DSDS17'; 'DSDS17 3MT'; 'Defence Studies'